Ketidaksetujuan terhadap Interpretasi Pendamaian Stoa dan Kekristenan dalam Pemikiran Justus Lipsius - Yohanes Theo (Sekolah Tinggi Filsafat Seminari Pineleng, 2023)
Justus Lipsius drew up an intellectual project to reconcile stoic thought with Christianity. In this project, Lipsius started with two assumptions. First, Stoicism's “divine fire” as the highest principle is to be explained by making reference to Scripture where God manifests himself through fire. Second, destiny is a manifestation and an expression of Divine Providence that plays an important part in concrete situations. Has Justus Lipsius been successful at reconciling the Stoics and Christianity? This paper is intended to address this question using a literature review approach. The author goes through the philosophical thoughts of neo-stoicism, Justus Lipsius. Basically, Stoicism showed differences to Christianity. Stoicians believe that the Divine is material. Destiny and divine providence become one. Both are a series of causes that bring matters to mechanical work. Consequently, the space for freedom is almost nonexistent because stoic humans wish to align themselves with Nature fully. Christianity tells the opposite. God is nonmaterial, and the nuances of human freedom are held in high regard. As a result, Lipsius could not reconcile the Stoics with Christianity.